Hallmarking: Narrating commercials through referencing animated films, live actions, and games - Purnomo, SF. Luthfie Arguby (Universitas Bunda Mulia, 2026)
I argue that audiovisual commercials that make references or incorporate portions of animated films, games, and live actions could be goggled from the perspectives of hallmark events. Through hallmark events, I argue that ones can reveal the strategies of incorporating events from the other audiovisual products into audiovisual commercials to make them narratively natural. I call these strategies hallmarking. To prove that hallmarking strategies are existent in these distinctive commercials, I employed the theories of hallmark events by Getz, Svensson, Peterssen, and Gunnervall, reference theory by Purnomo et al., the theory of television commercials as short film arts by Rhodes and Singer, and narrative negotiation by Kraus. Investigating twenty commercials ranging from animated films, games, and live actions, I argue that hallmark events could be employed to goggle how commercials incorporate animated films, games, and live actions – a phenomenon that I call hallmarking. I also argue that hallmarking has two functions namely momentum and ludic functions. These functions are delivered through three strategies of hallmarking namely matchmarking, touchmarking, and footmarking. These strategies could be employed as a guide or consideration in referencing, blending, or incorporating events in animated films, games, or live actions into audiovisual commercials.